2014
DOI: 10.4067/s0718-27242014000100007
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Priorities of the Pork Loin Supply Chain

Abstract: The pork meat production industry is facing new challenges as a consequence of consumers' expectations regarding the quality and safety of food products. For the present study, experts and consumers in Rio Grande do Sul State, Brazil were interviewed to identify the attributes of pork loin that need to be improved. Consumers have particular concerns about the juiciness, fibrousness, and portion size of the meat, the diversity of cuts and safety and animal welfare. The supply chain was also analyzed in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In contrast to the Europeans, Chinese urban citizens seem to prefer industrial farms [ 36 , 37 ], a response that was echoed by some Brazilian consumers [ 38 , 39 ]. The preference for large industrial farms in some countries, particularly in emerging economies, by pork consumers may be associated with the perception that sanitary conditions and food safety standards are higher on these types of farms [ 36 , 37 , 40 ]. In the current survey, cleanliness and sanitary aspects were also highly valued as desired features of an ideal pig farm.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the Europeans, Chinese urban citizens seem to prefer industrial farms [ 36 , 37 ], a response that was echoed by some Brazilian consumers [ 38 , 39 ]. The preference for large industrial farms in some countries, particularly in emerging economies, by pork consumers may be associated with the perception that sanitary conditions and food safety standards are higher on these types of farms [ 36 , 37 , 40 ]. In the current survey, cleanliness and sanitary aspects were also highly valued as desired features of an ideal pig farm.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the fact that Brazilian consumers perceive pork meat as a greater risk to health than beef [ 68 ]. Others have shown that, although some sensorial aspects, practicality and convenience and production following animal welfare standards are highly valued by Brazilian pork consumers, animal sanitary aspects are considered the most important [ 69 ]. Possibly due to historical and cultural images of early pork production systems that existed in the country [ 68 , 70 ], many Brazilians associate pork meat with a source of zoonotic diseases–especially worm infestations–and high cholesterol [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns, attitudes, and opinions of meat buyers in Garanhuns, Pernambuco, Brazil Dill et al Lino et al (2009) reported that the main factor influencing the purchase decision of consumers buying meat in the public markets of the city of Jaboatão dos Guararapes, located in the metropolitan region of Recife, Pernambuco, was price, followed by convenience, custom, and reliability of the product. Often, meat was no longer consumed due to the buyer's income, lack of availability and practicality of the food, and/or perceived health risks (Dill et al, 2014b). This concern about health risks may be associated with recent major scandals involving dubious suppliers who misrepresented their products to consumers (Boito et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Through the literature review, a preliminary questionnaire was developed with objective and subjective questions based on the TPB (Ajzen, 1991) and research related to consumer behavior (Yeung and Morris, 2001;McCarthy et al, 2003;Verbeke and Vackier, 2005;Barcellos, 2007;Verbeke et al, 2010;Barcellos et al, 2012;Diniz et al, 2013;Dill et al, 2014b). The questionnaire went through a pre-test with 10 specialists in the areas of consumer behavior, sanitation, and meat inspection and marketing, and 10 meat buyers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation